2021
DOI: 10.3390/antibiotics10080887
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Approaches for the Antileishmanial Activity Evaluations of Actinomycins Isolated from Novel Streptomyces smyrnaeus Strain UKAQ_23

Abstract: Leishmaniasis, a Neglected Tropical Parasitic Disease (NTPD), is induced by several Leishmania species and is disseminated through sandfly (Lutzomyia longipalpis) bites. The parasite has developed resistance to currently prescribed antileishmanial drugs, and it has become pertinent to the search for new antileishmanial agents. The current study aimed to investigate the in vitro and in silico antileishmanial activity of two newly sourced actinomycins, X2 and D, produced by the novel Streptomyces smyrnaeus strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Fourier transform infrared spectroscopy (FT-IR) revealed that the procured TQ had the same spectroscopic spectrum as the standard TQ ( Figures S1 and S2, see Supplementary Materials ) [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourier transform infrared spectroscopy (FT-IR) revealed that the procured TQ had the same spectroscopic spectrum as the standard TQ ( Figures S1 and S2, see Supplementary Materials ) [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Leishmaniasis is a neglected tropical parasitic disease (NTPD) disseminated by female phlebotomine sandflies. It is caused by various species of obligate intracellular Leishmania protozoan parasites [ 1 , 2 , 3 , 4 , 5 ]. In humans, the parasite grows and reproduces as an internal amastigote inside macrophage phagolysosomes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All systems were minimized for 5000 steps using the Steepest Descent technique, and convergence was achieved under the force limit of 1000 (kJ/mol/nm) to exclude any steric clashes. Later, all four minimized systems were separately equilibrated at NVT (Canonical ensemble: where moles, N; volume, V; and temperature, T were conserved) and NPT (Isothermal-Isobaric ensemble: where moles, N; pressure, P; and temperature, T were conserved) ensembles for 100 ps (50,000 steps) and 1000 ps (1,000,000 steps), respectively, using time steps 0.2 and 0.1 fs, at 300 K to ensure a fully converged systems for the production run [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…For each of the three complexes, the production was run for 200 ns. The trajectory and energy data were recorded every 10 ps [ 56 ]. GROMACS simulation package (GROMACS 2020.4) [ 57 , 58 ] was used to perform MD simulations using CHARMM36m forcefield [ 59 ].…”
Section: Methodsmentioning
confidence: 99%